THE TYPES OF REQUEST EXPRESSIONS USED IN NOVEL 'HARRY POTTER AND THE CHAMBER OF SECRETS': Their Appropriateness to ESL/EFL Teaching for Junior High School Students in Indonesia - Nuzulul Isna; Inong Permata Sari (Englisia: Journal of Language, Education, and Humanities, 2017)
Novels can be authentic sources for learning ESL/EFL, especially in non-English speaking countries. They may present reliable learning references in the absence of native speakers. This article aims to identify the types of request expressions originated in novel 'Harry Potter and the Chamber of Secrets' as well as their appropriateness for teaching ESL/EFL in aligment to current applied curriculum (2006 curriculum) in junior high school level in Indonesia. This research employed a qualitative research which was based on content analysis methodology. The data analysis revealed the types of request expressions (Tsui, 1989) generated out of 110 items uttered by the characters in the novel. 65.5% of the finding matched the nine request expressions learning materials embedded in the 2006 curriculum. Indeed, this finding may significantly contribute to the addition of authentic English learning source, especially in teaching speaking skill.